Bioluminescent Xanthomonas hortorum pv. gardneri as a Tool to Quantify Bacteria in Planta, Screen Germplasm, and Identify Infection Routes on Leaf Surfaces - Bernal, Eduardo; Deblais, Loïc; Rajashekara, Gireesh; Francis, David M. (Frontiers in Plant Science, 2021)
Imaging technology can provide insight into biological processes governing plant pathogen interactions. We created and used a bioluminescent strain of Xanthomonas hortorum pv. gardneri (Xgb) to quantify infection processes in plants using tomato as a model. X. hortorum pv. gardneri is one of four Xanthomonas species that causes bacterial spot in tomato. We used Xgb to quantify bacterial growth in planta, to assess disease severity in resistant and susceptible tomato lines, and to observe infection routes in leaves. A positive and significant linear correlation r(66)= 0.57, p ≤ 0.0001 was observed between bioluminescence signals emitted by Xgb in planta and bacterial populations determined through dilution plating. Based on bioluminescence imaging, resistant and susceptible tomato lines had significantly different average radiances. In addition, there was a positive and significant correlation r(10) = 0.45, p = 0.024 between X. hortorum pv. gardneri -inoculated tomato lines evaluated by bioluminescence imaging and tomatoes rated in the field using the Horsfall-Barrat Scale. Heritability was calculated to compare the genetic variance for disease severity using bioluminescence imaging and classical field ratings. The genetic variances were 25% and 63% for bioluminescence imaging and field ratings, respectively. The disadvantage of lower heritability attained by bioluminescence imaging may be offset by the advantage of completion of germplasm evaluation experiments within 30 days rather than 90-120 days in field trials. We further explored X. hortorum pv. gardneri infection routes on leaves using spray and dip inoculation techniques. Patterns of bioluminescence demonstrated that inoculation technique affected distribution of bacteria, an observation verified using scanning electron microscopy. We found significant non-random distributions of X. hortorum pv. gardneri on leaf surfaces. Method of inoculation affected bacterial distribution on leaf surfaces at 4 hours post inoculation (hpi). At 18 hpi, regardless of inoculation method, X. hortorum pv. gardneri localized on leaf edges near hydathodes based on bioluminescence imaging, an observation that was confirmed by electron microscopy. These findings demonstrated the utility of bioluminescent X. hortorum pv. gardneri to estimate bacterial populations in planta, to select for resistant germplasm, and to detect likely points of infection